Persoalan Proses Kalibrasi Model Perkiraan Banjir Daerah Aliran Sungai Besar Studi Kasus DAS Bengawan Solo - Sobriyah, Sobriyah (Department of Civil Engineering, Diponegoro University, 2004)
Rainfall runoff model with system approach do not interested of the process that happened on the land, but its more interested of the truth of the result which is obtained through calibration. The problem emerge and itsÂ started from the existing data condition. The existing of rainfall data have different range of time and it owning many empty data. The areal precipitation analysis by Thiessenâ€™s methode get difficulty because its polygon fluctuate. For large catchment with some place of Automatic Water Level station, the chosen of streamflow represent the time series of streamflow from the upstream to the downstream. Some gathered data indicate that the upstream hydrograf is high but the downstream hydrograf is low, or on the contrary. Most of Bojonegoroâ€™s hydrograph data has smaller volume than its upstream hydrograph. For the overcome of this problem its used the various method, so that result of calibrating is satisfy Key Words : calibration problem, rainfall-runoff model, large catchment